2013
DOI: 10.1111/kykl.12027
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Multinationals on the Size of the Banking System

Abstract: Summary After the global financial crisis, the size of the banking sector has become a hotly debated topic. To measure the size of the banking system a country's banking assets divided by the country's gross domestic product (GDP) is commonly applied as a general yardstick. This paper shows that this yardstick does not take into account differences in financial needs. In particular, countries differ with regard to the number and size of multinational enterprises. In a cross‐country empirical study, we find a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They often work for the mutual interest of their members and additionally support the local development of their area. Furthermore, the recent financial crisis has questioned the large size of banks (Schoenmaker and Werkhoven ) and the mainstream banking models (Groeneveld and de Vries ). Different studies have demonstrated the importance to preserve institutional diversity (Hesse and Cihák ; Ayadi et al ; Liikanen et al ; Ferri et al ).…”
Section: Introductionmentioning
confidence: 99%
“…They often work for the mutual interest of their members and additionally support the local development of their area. Furthermore, the recent financial crisis has questioned the large size of banks (Schoenmaker and Werkhoven ) and the mainstream banking models (Groeneveld and de Vries ). Different studies have demonstrated the importance to preserve institutional diversity (Hesse and Cihák ; Ayadi et al ; Liikanen et al ; Ferri et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The value-added of this sector amounts to almost 8% of the GDP and is even higher now than in the pre-crisis period ( Figure 13). While some business operations are justified by the fact that banks have continued to serve large multinational Dutch companies abroad (Schoenmaker and Werkhoven, 2013), this explains only a small part of the growth in international activities. Financial internationalisation has proven to be profitable in the short-run, but it has led to an extensive exposure to cross-border risks.…”
Section: Reducing Risks From a Large And Concentrated Banking Sectormentioning
confidence: 99%